Aspectos etnozoológicos sobre os crustáceos estomatópodes e decápodes das praias do litoral norte da Bahia, Brasil - Silva, Felipe Paganelly Maciel da (2014)
The aim of the study was to register the ethnozoological corpus that artisanal fishermen communities on Bahia’s North shore have about stomatopod and decapod crustaceans, as well as to investigate the different ways that these animals are locally used. The fieldwork was conducted in two stages: the first consisted on the collection of biological material; later, expeditions were made aiming to collect ethnozoological data through semi-structured interviews about the crustacean specimenspreviously collected. The northern and southern boundaries of the study area were the beaches of Ipitanga and Mangue Seco, respectively, totalizing 23 sampling points for biological material collection. A total of 51 interviews were conducted on the beaches of Vilas do Atlântico, Buraquinho, Jauá, Arembepe and Praia do Forte from August to December 2013.Fishermen on the North coast of Bahia feature a diverse conception of crustaceans, with an impressive wealth of perceptions, using several criteria to define/identify the group, such as morphological, physiological, ecological, and usage criteria. From these criteria, the fishermen cited a total of 42 names, including crustaceans and other animals belonging to different taxonomic groups, such as octopuses, echinoderms and even sea turtles. Referring to body topography, homologous structures presented similar names in different crustaceans, demonstrating a recognition degree of analog systems by traditional knowledge. The fishermen featured knowledge about physiological, reproductive and seasonal processes of crustaceans. About the fishing techniques, in the study area artisanal fishermen use a total of ten fishing gears, where lobsters (Panulirus laevicauda) were the most wanted source, followed by the sapateira crab (Parribacus antarticus). Other crustaceans showed no commercial interest and some species are eventually caught for subsistence. Referring to the ways of use, the following usages were recorded: feed and commerce, fishing artifact (bait), medicinal, and esthetical-decorative. The interviewed fishermen recognized, unanimously, the importance of crustaceans for the environment. Their folk knowledge could interfere in conservation measures, since the perception of improvement and preservation of the marine ecosystem by the presence of crustaceans may influence on the sustainability of the fishing activity.